DEVELOPMENT OF TRADITIONAL LIFE AND TRADITIONS IN GAMPONG LAMREUNG, ACEH BESAR DISTRIC - Sutri Helfianti; Mudhafar Anzari; Zulfan Zulfan (Universitas Muhammadiyah Aceh, 2023)
Qanun Number 9 of 2008 concerning the Development of Traditional Life and Customs provides 18 (eighteen) types of trials/disputes in which there are rules regarding minor offences being the authority of customary licenses while including serious criminal offences beyond traditional justice. The objective of this community service is to provide understanding to the people of Gampong Lamreung, Darul Imarah subdistrict, regarding Qanun Number 9 of 2008 concerning the Development of Traditional Life and Customs, as well as what efforts officials of the gampong and the community can make in dealing with minor crimes in Gampong Lamreung, Darul Imarah of Aceh Besar Regency. The methods used in this community service are in the form of counseling, lectures and questions and answers regarding the importance of Qanun Number 9 of 2008 concerning the Development of Traditional Life and Customs. The Aceh government has attempted to protect traditional life and customs through Qanun Number 9 of 2008 concerning the Development of Traditional Life and Customs. However, this Qanun is only known to government institutions and traditional leaders, even though the target of fostering and developing traditional life and customs is also aimed at the family circle, which is an important component in maintaining and preserving the development of Aceh's traditional life and customs.The follow-up to this community service is carrying out the same activities focused on the family environment. This is aimed so that the development of traditional life and customs can be implemented effectively.Keywords: Qanun, Tradition and Custom, Family